2020
DOI: 10.1002/jso.26184
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes for hepatocellular carcinoma detected after hepatitis C virus eradiation by direct‐acting antivirals

Abstract: Objective: To investigate the postoperative recurrence of hepatitis C virus (HCV)-related hepatocellular carcinoma (HCC) after liver resection in patients with and without the achievement of sustained virologic response (SVR) through the administration of direct-acting antivirals (DAA). Methods: Among 28 patients with HCC detected after DAA-SVR (DAA group) and 197 patients with HCC who did not receive treatment for HCV infection or who did not achieve an SVR (control group) between January 2000 and July 2019, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
(89 reference statements)
0
10
0
Order By: Relevance
“…Results of a previous study of propensity score-matched cohorts indicated that the rate of disease-free survival was better in patients with HCC detected after DAA-induced SVR than in those without SVR or HCV treatment. 11 In this study, the disease-free survival rate after liver resection was better in the DAA-HCC group than in the control group according to univariable analysis but not according to multivariable analysis. Exclusion of patients with HCC recurrence within 1 year after liver resection might have weakened the difference between the two groups.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Results of a previous study of propensity score-matched cohorts indicated that the rate of disease-free survival was better in patients with HCC detected after DAA-induced SVR than in those without SVR or HCV treatment. 11 In this study, the disease-free survival rate after liver resection was better in the DAA-HCC group than in the control group according to univariable analysis but not according to multivariable analysis. Exclusion of patients with HCC recurrence within 1 year after liver resection might have weakened the difference between the two groups.…”
Section: Discussionmentioning
confidence: 52%
“…9,10 Results of a previous study indicated that in patients in whom HCC was detected after DAA-induced SVR, this treatment suppressed postoperative recurrence, in comparison with patients who did not receive antiviral drugs or those without DAA-or IBTinduced SVR. 11 However, the effect of DAA-induced SVR after treatment, including liver resection, has been controversial; some recent studies have shown unexpected high recurrence rates after DAA therapy, 12,13 whereas other studies have demonstrated contradictory findings. [14][15][16][17][18][19][20][21] Several problems such as the timing of DAA therapy and heterogenous characteristics of patients were indicated as the causes of discrepancies, but of much more importance is whether postoperative recurrence and prognosis after liver resection in patients with postoperative DAA-induced SVR are similar to those in patients in whom HCC was detected after DAA-induced SVR and better than those in patients without DAA-induced SVR.…”
Section: Introductionmentioning
confidence: 99%
“…1,22 By contrast, chronic hepatitis C is much more common in Japan, and sustained viral responses might not be high in the study patients considering the recent introduction of direct acting antiviral agents. 23,24 The findings of this study suggest that inferior outcomes in Japanese patients may be associated with older age, poorer liver function, more frequent hepatitis C virus infection, and more aggressive tumor biology.…”
Section: Discussionmentioning
confidence: 83%
“…Our study analyzed the real‐world survival advantages of antiviral agents (DAAs or IFN) in patients with HCV who underwent liver resection for primary HCC. A number of recent studies evaluated the survival advantages and recurrence rate following HCV therapy in individuals with surgically treated HCC 9,50–53 . Osaka group reported long‐term outcomes of patients with surgically treated HCC following HCV therapy (mostly IFN 50,51 and a small patient number of DAAs 52 ).…”
Section: Discussionmentioning
confidence: 99%